BRANDING INNOVATION OF SMALL AND MEDIUM MICRO BUSINESS PRODUCTS KAMPOENG BATIK JETIS SIDOARJO - Aphief Tri Artanto; Aryo Bayu Wibisono; Arista Pratama; Laksmi Diana (Journal of Economics, Business, and Government Challenges, 2021)
The role of micro, small and medium enterprises is very important in the effort to build the economy in Indonesia in the era of disruption because of its significant contribution to job creation and improving people's welfare. Problems that often arise in micro, small and medium enterprises include limited capital, lack of innovation, inaccurate distribution/distribution (conventional marketing, inadequate innovation, inefficient in managing finances, technology ignorance so that online marketing is not optimal). The objectives of this research are (a) to describe the product branding innovation of micro, small and medium enterprises of Kampoeng batik Jetis Sidoarjo Regency; (b) describe the supporting factors and the inhibiting factors for the branding innovation of the micro, small and medium enterprises of Kampoeng Batik Jetis Sidoarjo Regency. The research, which is located in Kampoeng Batik Jetis Sidoarjo, uses qualitative research methods. The reason for choosing this topic is that the micro, small and medium enterprises of Kampoeng Batik Jetis Sidoarjo Regency are limited in the management of their business branding so that their marketing is limited. The conclusions of the present research are 1) The innovation of product branding for micro, small and medium enterprises of Kampoeng Batik Jetis Sidoarjo Regency has not been carried out optimally. Jetis batik craftsmen in Sidoarjo Regency tend to follow their predecessors. Branding is built by providing logos, opening galleries, opening batik training, giving good service, giving craftsmen business cards. 2) The factors that support the product branding innovation of Kampoeng Batik Jetis Sidoarjo Regency are (a) very high market potential; (a) The selling price is relatively affordable to the public; (c) is a unique product; (d) Has unique characteristics; (e) The government is committed to developing micro, small and medium enterprises; (f) the not yet mushrooming of batik handicrafts in Indonesia; and (g) Opened market share.